Contractual Performance Facing Covid-19: A Comparative Analysis - Zafer Kahraman (Annales de la Faculté de Droit d’Istanbul)
Covid-19 is a social disaster, an unforeseen and unavoidable event affecting most of the pre-existing contracts, which has occurred beyond the control of the parties. The drastic measures taken by governments to protect public health, emanated some radical changes in the circumstances on which most of the contracts were based. The impact of Covid-19 differs in various contracts. It adversely affects some of the contracts by preventing or impeding the disadvantaged party to perform, whereas in some other cases it causes a radical change in circumstances generating an excessive difficulty to the fulfillment of the contract, which renders performance unreasonable and the contract unfair. It is also possible that the contract might even not be affected by the pandemic. In short, it renders some contracts impossible and for some others, it makes them unreasonably difficult to perform. This article focuses on the agreements “infected” by the Covid-19 pandemic, by studying its legal implications. Within the framework of this article, the legal nature of the pandemic will be presented and its impact on the contracts will be discussed. The aim is to provide both academic analysis and an idea of the way civil law and common law systems are coping.